Stimulation of Preschool Motor Development Through Brain Gym and Puzzle - Panzilion, Panzilion; Padila, Padila; Setyawati, Asih Dewi; J, Harsismanto; Sartika, Andry (JOSING: Journal of Nursing and Health, 2020)
The purpose of this study was to determine the effectiveness of brain Gymnastics and playing puzzles on improving the motor skills in preschool children in the work area of the Basuki Rahmad Health Center in Bengkulu. The Quantitative research design used the quasy experiment design, one group pre-post test equivalent without control design. The results of the univariate analysis with brain gymnastics and playing puzzles intervention showed the 15 respondents before doing brain gymnastics and puzzle, there were nine children (60%) experiencing motor skills deviations and after giving therapy ten children (66.7%) experienced standard motor skills. The bivariate results of the Wilcoxon test have a significant effect between before and after brain gymnastics and puzzle intervention with p-value = 0.001 on motor development at the preschool children. It can conclude that an increase in the average motor picture before and after brain gymnastics and playing puzzles interventions in the Basuki Rahmad Community Health Center in Bengkulu. Keywords: Brain gym, Puzzle, Motor, Preschool